A review on the role of footwear design in archery: insole design considerations & fabrications - Kamaruddin, Siti Ruzimah; Dolah, Mohd Shahrizal; Abd Rahman, Ahmad Rizal; Mon, Redee Sut Txi (Asian Scholars Network, 2026)
This review synthesizes current research on the biomechanics of archery stance, with a focus on footwear design attributes and their influence on performance and injury prevention. By reviewing methodologies such as motion capture, plantar pressure mapping, and material testing, footwear features including arch support, sole rigidity, and traction, among others, impact postural stability, weight distribution, and kinetic efficiency, which are crucial during archery. Key findings highlight that footwear innovations, such as contoured arch supports and energy-return midsoles, improve shooting consistency and mitigate risks of overuse injuries. Customized designs, including cast and 3D-printed insoles with load distribution structures, enhance stance stability by optimizing foot alignment and redistributing plantar pressure. Advanced nanocomposite materials demonstrate potential for durable energy retention. The review underscores footwear as a critical biomechanical interface, bridging theoretical principles and practical design applications. By contextualizing these advancements, this review identifies gaps in personalized design protocols and calls for interdisciplinary collaboration to translate biomechanical insights into performance enhancing, injury-resilient footwear for archers.